THE EFFECTS OF GADGETS ON THE OCCURRENCE OF ANEMIA IN TEENAGE GIRLS - Juhrotun Nisa; Adevia Maulidya Chikmah; Riska Arsita Harnawati (Siklus : Journal Research Midwifery Politeknik Tegal, 2020)
The prevalence of anemia in Indonesia, namely in teenager women, was 26.50% and in women of childbearing age by 26.9%. In addition to eating patterns, teenagers were now starting to depend on the development of existing technology. Lifestyle had an impact on the incidence of anemia. The purpose of this study was to determine the effect of gadgets on the incidence of anemia in teenager girls. This research was an analytical survey study with a cross-sectional design, conducted from June to August 2019 at SMK 1 Kota Tegal. The sampling technique used was total sampling with a sample of 40 young women in the Department of Catering. Data collection in this study used a questionnaire, while data analysis was carried out univariate and bivariate with chi-square. The results showed that the use of gadgets for 4-5 hours/day had anemia as much as 55.6%, and 78.9% of anemia in the use of gadget 2-3 hours/day. The use of gadgets with a duration of 4-5 hours/day and poor eating patterns as much as 88.9% and 57.9% of respondents on the duration of use of 2-3 hours/day. There is an influence between the duration of the use of gadgets on eating patterns (p-value = 0.005), and there is an influence between the use of gadgets on the incidence of anemia (p-value = 0.037). The more widespread use of gadgets, it is necessary to have support from across sectors such as teachers and parents always to remind and limit smartphone usage. Keywords             : Gadgets, anemia